2013
DOI: 10.1556/aagr.61.2013.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Role of salicylic acid in acclimation to low temperature

Abstract: Low temperature is one of the most important limiting factors for plant growth throughout the world. Exposure to low temperature may cause various phenotypic and physiological symptoms, and may result in oxidative stress, leading to loss of membrane integrity and to the impairment of photosynthesis and general metabolic processes. Salicylic acid (SA), a phenolic compound produced by a wide range of plant species, may participate in many physiological and metabolic reactions in plants. It has been shown that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…, Pál et al. ). Most of the results describing cold acclimation mechanisms are achieved using different plant species, especially model plant Arabidopsis .…”
Section: Discussionmentioning
confidence: 97%
“…, Pál et al. ). Most of the results describing cold acclimation mechanisms are achieved using different plant species, especially model plant Arabidopsis .…”
Section: Discussionmentioning
confidence: 97%
“…These molecules trigged the expression of the potential to tolerate stress rather than having any direct effect as a protectant. While reviewing a number of studies, Pál et al (2013) concluded that SA protects the plant from chilling stress by modifying the antioxidant capacity, changing expression rates of certain genes, and by playing a key role in acclimation process.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it may greatly delay seedlings emergence, development, establishment, and cause serious chilling injuries as well as infection diseases resulting in a significant reduction in yield and low seed quality. Chilling may also induce diverse phenotypic and physiological symptoms, leading to oxidative stress and loss of membrane integrity, which may disrupt general metabolic processes (Pál et al 2013). Moreover, the exposure to low temperature has harmful effect on photosynthesis and photosystem II (PS II) which is especially susceptible to injuries.…”
mentioning
confidence: 99%